Glyptothorax ketambe, a new catfish (Teleostei: Sisoridae) from northern Sumatra - Ng, Heok Hee; Hadiaty, Renny K. (Zootaxa, 2009)
Glyptothorax ketambe, a new species of sisorid catfish is described from the Alas River drainage in Nangroe Aceh Darussalam Province, northern Sumatra. Glyptothorax ketambe can be distinguished from all other Sundaic congeners except G. schmidti and G. siamensis in having a color pattern consisting of a dark brown body with yellowish midlateral and mid-dorsal stripes. It differs from G. schmidti and G. siamensis in having a combination of: caudal-peduncle depth 7.6–8.9% SL, head width 16.1–17.9% SL, thoracic adhesive apparatus not reaching to the level of the base of the last pectoral-fin ray, and thoracic adhesive apparatus with an almost straight lateral margin. The identity of G. schmidti is also clarified in this study.